2023
DOI: 10.1186/s41100-023-00468-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors related to depression in peritoneal dialysis patients: a multicenter cross-sectional study

Abstract: Background End-stage renal disease (ESRD) is serious global public health challenge in many developing countries. Treatment of ESRD is carried out through renal replacement therapy like peritoneal dialysis (PD). Depression is the most common mood disorder which has a strong impact on the quality of life in patients with ESRD. Little is known about the prevalence and risk factors of depression in peritoneal dialysis patients. Method and materials A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…This perception might influence individuals to opt for MoH or other governmental sector hospitals for renal dialysis services instead of private-sector hospitals. Alhamad et al found that patients consider transportation means, family, and social support when selecting dialysis centers, aligning with the current findings consistent with the current outcome [ 23 25 ]. In line with Friberg et al’s research, patients were more inclined towards home dialysis, receiving comprehensive and high-quality information about predialysis from three or more sources [ 26 – 28 ].…”
Section: Discussionsupporting
confidence: 84%
“…This perception might influence individuals to opt for MoH or other governmental sector hospitals for renal dialysis services instead of private-sector hospitals. Alhamad et al found that patients consider transportation means, family, and social support when selecting dialysis centers, aligning with the current findings consistent with the current outcome [ 23 25 ]. In line with Friberg et al’s research, patients were more inclined towards home dialysis, receiving comprehensive and high-quality information about predialysis from three or more sources [ 26 – 28 ].…”
Section: Discussionsupporting
confidence: 84%
“…Fernandez et al, reported that if the prevalence of depression and anxiety is compared between the general population and HD patients, the latter will definitely have a greater prevalence of these two mental diseases (Fernandez et al, 2022). Various studies found a different incidence of depression among dialysis patients (Dong et al, 2016;Bazazzadeh et al, 2023). Based on data from the World Health Organization (WHO), worldwide prevalence rates of depression and anxiety in 2015 have been determined to be 4.4 and 3.6%, respectively (World Health Organization, 2017).…”
mentioning
confidence: 99%
“…What’s more, most depression patients are easily ignored and inadequately treated in the past decade. Previous studies only assessed the relationship of depression and PD patients at the baseline [ 16 ]. In addition, published evidence that examined depression levels impacting clinical outcome including mortality risk, has only included patients on hemodialysis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%